2020
DOI: 10.1111/resp.13879
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in Saudi Arabia: First data from the SAUDIPH registry with a focus on pulmonary arterial hypertension

Abstract: Background and objective This study presents the first results of ‘SAUDIPH’ registry, aiming to assess patient characteristics, treatment approach and clinical and survival outcomes in patients with PAH. Methods The registry enrolled patients with Group 1 and Group 4 PH under clinical management in a specialized tertiary care centre from 2004 to 2018. Changes from baseline to last follow‐up visit were assessed. Results A total of 222 patients were enrolled, and Group 1 PH was the most frequent aetiology (57.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
3
7
1
Order By: Relevance
“…In our study, we could not confirm previous findings that evidenced very young ages at diagnosis, in PAH patients with positive gene mutations, except for those with EIF2AK4 mutations 14 . The median age at diagnosis of the patients with gene mutations (29.5 years) is in agreement with previous reports on the Saudi Arabia PAH population 24 …”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…In our study, we could not confirm previous findings that evidenced very young ages at diagnosis, in PAH patients with positive gene mutations, except for those with EIF2AK4 mutations 14 . The median age at diagnosis of the patients with gene mutations (29.5 years) is in agreement with previous reports on the Saudi Arabia PAH population 24 …”
Section: Discussioncontrasting
confidence: 74%
“…14 The median age at diagnosis of the patients with gene mutations (29.5 years) is in agreement with previous reports on the Saudi Arabia PAH population. 24 Regarding disease severity, our results showed a tendency for higher disease severity in patients with positive mutations, mainly in those with mutations in EIF2AK4. In fact, even though our patients with mutations were equally distributed between WHO FC II and III/IV, 6MWD, NT-proBNP, and hemodynamic parameters (cardiac index (CI), mean pulmonary arterial pressure (mPAP) and mean right atrial pressure (mRAP)) are indicative of a uncontrolled disease, as reported by Pfarr et al 14 Mutations were identified in 30% of the IPAH patients and in 100% of the PVOD patients (n ¼ 2).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…than 6 months before enrolment, while prevalent cases were regarded as those who had already received a diagnosis of PAH and started targeted therapy more than 6 months prior to enrolment. 15,16 Initial combination therapy was defined as initiating two or more PAH-targeted drugs at the start of targeted treatment in newly diagnosed and treatment-naive patients. 8 Diagnostic interval was calculated as the period between symptom onset and diagnosis of PAH by RHC.…”
Section: Summary At a Glancementioning
confidence: 99%